Motoric Development of Children Through a Variety of Greetings - Taat Kurnita Yeniningsih; Nelvi Maulid; Hayati Hayati; Aida Fitri; Israwati Israwati; Dani Sukma Agus Setiawan; M. Syukri Azwar Lubis (JURNAL SERAMBI ILMU, 2021)
Types of greetings are the kinds of movements that result from the greeting process in the form of greetings to someone / another person which will have an impact on the child's motoric skills from the various greeting movements. Variety of greetings is synonymous with the diversity produced by the greeting itself, thus creating gestures similar to greetings. The kinds of greetings referred to are in the form of Assalamu'alaikum, movements of shaking hands, gestures of hugs and clapping movements. The purpose of this study was to determine children's motoric development through the application of various greetings at IT Mon Kuta Kindergarten in Lambhuk Village, Banda Aceh. This research uses qualitative research with a descriptive approach. Data collection techniques, namely through interviews and observations. The data analysis technique in this study is a collection of data that has been obtained from the results of children's observations that researchers have done since the beginning of each aspect of research activities, the results that have been collected are entered into the observation sheet. The results showed that the children's motoric development had started well. The motoric development of the child is done through a variety of ways, namely that the child can mimic movements and control movements. So, through various greetings activities can develop children's motoric aspects.